The Horizontal Curved Geometric Design with Autocad® Civil 3D on Jalan Muara Wahau, East Kalimantan - Annisa Megarestya; Andri Irfan Rifai; Muhammad Isradi (Indonesian Journal of Multidisciplinary Science, 2022)
Roads connect one area to another. Therefore, an excellent geometric design of the road can reduce the percentage of accidents. For this reason, AutoCAD Civil 3D® is used as a means of planning. This road planning aims to plan the horizontal alignment of the road connecting the main road with kpc Tanjung bara (coal port). This street is located on Jalan Poros Muara Wahau, East Kalimantan. This study used secondary data obtained through google earth and global mapper. Then the data is processed using qualitative research methods. This study found that the road section length was 6,086 m or 6,086 km (STA 0 + 000 – 6 + 086). Bends P1 on (STA 2+680 – 3+260) are planned with the type S-C-S bend. The bend has an R of 600 meters, an e of 4.3%, and a Ls of 119 meters.